The Perception of Substance Use Disorder Among Clinicians, Caregivers and Family Members of Individuals With Intellectual and Developmental Disabilities. Issue 1 (2nd January 2018) - VanDerNagel, Joanne E. L.; van Duijvenbode, Neomi; Ruedrich, Stephen; Ayu, Astri P.; Schellekens, Arnt F. A.
ABSTRACT: Introduction : Substance use disorders (SUD) are common among individuals with intellectual and developmental disorders (IDD). The quality of care individuals with these conditions receive can be affected by perceptions and attributions of SUD among clinicians, professional caregivers, and family members. The aim of this study was to explore such perceptions and attributions. Method : We conducted a web-based survey using snowball sampling. The Illness Perception Questionnaire Revised (IPQ-R) was used to assess SUD perceptions and attributions. Our sample consisted of 88 clinicians (53.3%), 58 caregivers (35.2%), and 19 adult family members (11.5%), mostly from the United States (73.3%). Results : Respondents—especially clinicians—indicated having a clear concept of the nature of SUD. They recognize that SUD has major consequences for the client, but are positive about the influence both the client and treatment can have on its course and outcome. SUD is attributed to psychological factors (especially so by clinicians and professional caregivers), including stress and worries, and personality, as well as to general risk factors, including hereditary and behavioral factors. Conclusion : According to our respondents, SUD is a serious condition with major consequences, and a variety of potential causes. Given the high prevalence of substance use in the ID population, this calls for more attention for identification, prevention, and treatment of SUD. This includes improving access to SUD treatment adapted to the needs of individuals with IDD, improving coping and emotional skills, and promoting a fulfilling life with adequate social support.